Donald Trump, Adolf Hitler and the Naming of the Shrew: On Abusive Influence on the Language of Science by Political Leadership - Engelmann, Lars (Satura, 2020)
On March 3, 1942 Adolf Hitler read a newspaper article in the Berliner Morgenpost which agitated him. He ordered Martin Bormann, head of the Nazi Party’s head office, one of Hitler’s most trusted deputies and unofficially the second most powerful man in Germany at the time, to write the following letter to the chief of the Reich Chancellery Hans Lammers...